Dengue fever among febrile patients in Taiz City, Yemen during the 2016 war: Clinical manifestations, risk factors, and patients knowledge, attitudes, and practices toward the disease - KhairAlah A. Alghazali; Boon-Teong Teoh; Sing-Sin Sam; Juraina Abd-Jamil; Jefree Johari; Wahib M. Atroosh; Mohammed A. K. Mahdy; Sazaly AbuBakar (Elsevier, 2020)
The current war in Yemen has displaced millions of people from their homes into living in cramped shelters where the healthcare is limited. The breakdown of Yemen's healthcare and sanitation systems has facilitated the spread of infectious diseases including mosquito-borne diseases. The present study aimed to describe the prevalence of dengue virus (DENV) infection among the febrile patients of the Taiz governorate, Yemen as well as their knowledge, attitude and preventive practices (KAPs) regarding dengue fever (DF), and to investigate the factors associated with dengue preventive practices during the war. A total of 384 clinically dengue-suspected patients who sought health care in Taiz, Yemen during the period from July 2016 until October 2016 were recruited for the study. Serum samples were obtained and screened for the presence of DENV RNA and anti-DENV antibodies by reverse transcription-recombinase polymerase amplification (RT-RPA) and dengue IgM/IgG-capture ELISA, respectively. KAP questionnaires were obtained from all participants too. In the study, dengue was laboratory confirmed in approximately 49.3% (189/384) of the clinically suspected dengue patients. In general, 67.1% of the patients had low knowledge scores regarding DF. Low scores for knowledge about DF was significantly associated with those in the age groups of ?20 years and 21-30 years, illiterates and patients with non-skilled jobs or jobless. The most common preventive practices reported by participants were covering stored water (78.6%) and putting a screen on the house's windows (65.3%). A low proportion of participants (6.7%) had 51-100% of good DF preventive practices. Low scores of positive attitudes toward DF was identified as a risk factor. The study participants showed poor knowledge about DF and their ways of dealing with the various aspects of DF prevention was quite limited, hence, preventive measures against the disease were less likely to be undertaken. Findings from the study highlight the peril of dengue in Taiz, Yemen, which is now comparable to that of endemic regions. The ongoing civil war with disruption in regular health services compounded by the low knowledge about DF as well as the limited DF preventive practices could result in entrenchment of dengue in Yemen.